Long-term follow-up after weight management in obese cats - Deagle, Gabrielle (J Nutr Sci, 2014)
Feline obesity is a prevalent medical disease and the main therapeutic strategy is dietary energy restriction. However, at present there are no data regarding long-term outcome in this species. The purpose of the present study was to investigate if, as in other species, some cats regain weight following successful weight loss, and to identify any influencing factors in a cohort of client-owned cats with naturally occurring obesity. Twenty-six cats were included, all of which had successfully completed a weight management programme. After weight loss, cats were periodically monitored. The median duration of follow-up was 954 d (72–2162 d). Ten cats (39 %) maintained their completion weight (±5 %), four (15 %) lost >5 % additional weight and 12 (46 %) gained >5 % weight. Seven of the rebounding cats (58 %) regained over 50 % of their original weight lost. Older cats were less likely to regain weight than younger cats (P = 0·024); with an approximately linear negative association between the cat's age and the amount of weight regained (Kendall's τ = −0·340, P = 0·016). Furthermore, cats whose energy intake during weight loss was greater were also more likely to regain weight (P = 0·023). When the characteristics of weight regain in cats were compared with those from a similar cohort of dogs, cats that rebounded were more likely to regain >50 % of the weight they had lost. These results suggest that weight regain, after successful weight loss, is common in obese cats, and that young cats (<7 years of age) are most at risk.